THE VARIOUS ROLES OF REPETITION IN FEMALE EFL TEACHERS’ SPOKEN DISCOURSE - Abdul Karim; Sultan Baa (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research focuses on analyzing the various roles of repetition that appear in female EFL teachers’ spoken discourse. The subjects were two English teachers who teach Senior High Schools in Gowa Regency. They were taken by using deliberate or purposive sampling. The details were, each teacher was from SMA INSAN CENDEKIA SYECH YUSUF GOWA. The research instruments were interview, video recording, and documentations. Based on data analysis, it gathered several results; first, there were five roles of repetition which frequently appeared in the teachers spoken discourse namely, repetition as participatory listenership, ratifying listenership, expanding, evaluation through patterned rhythm, and humor (Tannen, 2007), from which expanding was the most dominant. Second, the female EFL teachers decide to employ or implement various roles of repetition in their oral communication through three phases, namely identification, determination, and evaluation (Simon, 1977). Having those findings, it is highly supported that by doing repetition properly in the teaching and learning process particularly in English encourages the teachers to maintain more vivid circumstances in their teaching particularly to maintain the students’ focus and the clarity of explanation